2009
DOI: 10.1038/ijo.2009.179
|View full text |Cite
|
Sign up to set email alerts
|

Associations between dietary patterns and obesity phenotypes

Abstract: Objective: To examine whether dietary patterns are associated with obesity phenotypes. Design: Cross-sectional study. Subjects: We recruited 664 participants aged between 18 and 55 years. Dietary data were collected from a food frequency questionnaire. A factor analysis was performed to derive dietary patterns. Body mass index (BMI), weight and waist girth were recorded using standard procedures. Fat mass and fat-free mass were assessed by electrical bioimpedance. Obesity was defined as having a BMIX30 kg m À2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
94
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 117 publications
(117 citation statements)
references
References 44 publications
17
94
2
1
Order By: Relevance
“…In contrast to free sugars, there is a controversy about the association between starch consumption and obesity among studies because starch is a complex carbohydrate mostly present in solid foods with fiber and other food components [34,44]. The combination of obesity-inducing nutrients and those protecting against body fat accumulation in this nutrient pattern makes interpretation somewhat difficult; however, taken together, our findings on the association between nutrient patterns and obesity support previous findings on the link between dietary patterns and obesity [45][46][47], and underline the validity of the nutrient pattern approach in assessing diet-disease relations. Furthermore, our findings indicate that complex, previously unrecognized, interactions may take place between highly loaded nutrients (both obesity-inducing and protective) that require much further research.…”
Section: Discussionsupporting
confidence: 69%
“…In contrast to free sugars, there is a controversy about the association between starch consumption and obesity among studies because starch is a complex carbohydrate mostly present in solid foods with fiber and other food components [34,44]. The combination of obesity-inducing nutrients and those protecting against body fat accumulation in this nutrient pattern makes interpretation somewhat difficult; however, taken together, our findings on the association between nutrient patterns and obesity support previous findings on the link between dietary patterns and obesity [45][46][47], and underline the validity of the nutrient pattern approach in assessing diet-disease relations. Furthermore, our findings indicate that complex, previously unrecognized, interactions may take place between highly loaded nutrients (both obesity-inducing and protective) that require much further research.…”
Section: Discussionsupporting
confidence: 69%
“…However, both expert opinion on healthy foods and the food consumption patterns of healthy eaters are influenced not only by nutritional characteristics of foods but also by individual, socioeconomic, and cultural considerations [37, [12] identified class of foods based on their nutrient profiles, and yogurt was included in "Class 1" containing the healthiest food choices alongside with fruits and vegetables. Paradis et al [15] have identified two dietary patterns using a 91-item FFQ, the Prudent and the Western dietary patterns, and have identified regular dairy products (including high-fat yogurt) as being part of the Prudent dietary pattern. The same research group has also shown that individuals having a high score of the Prudent pattern were less likely to be obese and in the opposite, those having a high score of Western pattern were more likely to be obese [15].…”
Section: Discussionmentioning
confidence: 99%
“…Paradis et al [15] have identified two dietary patterns using a 91-item FFQ, the Prudent and the Western dietary patterns, and have identified regular dairy products (including high-fat yogurt) as being part of the Prudent dietary pattern. The same research group has also shown that individuals having a high score of the Prudent pattern were less likely to be obese and in the opposite, those having a high score of Western pattern were more likely to be obese [15]. In the present study, yogurt (all types, independently of their fat content) was a contributor to the Prudent dietary pattern and consumers had a positive Prudent dietary pattern score, while the opposite was demonstrated in non-consumers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…None of the participants were excluded. Recruitment occurred between 2004 and 2006 through public advertisements (local newspapers and electronic messages) sent to university and hospital employees, as described previously [54]. A trained research assistant took anthropometric measures [54].…”
Section: Methodsmentioning
confidence: 99%